ANALISIS KINERJA KEUANGAN PADA KOPERASI SIMPAN PINJAM KARYA SAMATURU KOTA KENDARI - Sahyunu, Sahyunu; Utha, Rasidin; Hayani, Nur (Fakultas Ekonomi Dan Bisnis Universitas Sulawesi Tenggara, 2023)
This study aims to determine the financial performance of the savings and loan cooperatives Karya Samaturu Kendari City. The type of research used in this research is quantitative. The data processed is the financial statements of the savings and loan cooperatives of Samaturu in the 2021 Balance Sheet and Profit and Loss Report. The data collection techniques used are documentation techniques and library techniques. Technical analysis of the data used in this research is quantitative with the formula: Liquidity Ratio, Solvency Ratio, Profitability Ratio. The results showed that in general the financial performance of the Karya Samaturu Savings and Loan Cooperative, Kendari City, was good in managing the finances of the Samaturu Cooperative. This can be seen from the results of the calculation of the Liquidity Ratio categorized as very good, namely 228.5% where the standard is at a value of 200-250% (very good). The first Solvency Ratio measured using the Debt to Asset Ratio shows a good value, namely from Rp. 100.00 cooperative assets, 40.45% are financed by debt and 59.55% are financed by capital where the standard is > 40% - 50% ( good), the second Solvency Ratio measured using the Debt to Equity Ratio shows a very good value, namely every Rp. 62.94 of debt is guaranteed by Rp. 100.00 of invested capital, where the standard is at <70% (very good). And the first Profitability Ratio measured using Return on Assets shows a fairly good value, namely 5.99%, meaning that every Rp. 1.00 of total cooperative assets can generate a profit of Rp. 0.0599 where the standard is at 3% - <7% ( pretty good). The second is the Profitability Ratio measured using Return on Equity which shows a fairly good value of 11.19% meaning, every Rp. 1.00 of own capital the cooperative can generate a profit of Rp. 0.0112. Where is the standard 9% - <15% (good enough). The third is the Profitability Ratio measured using the Net Profit Margin showing an unfavorable value of 2.48%. That is, every Rp. 1.00 of income generates a net profit (SHU) of Rp. 0.0248. And is at the standard 1% - <5% (not good). Because the higher the NPM, the cooperative is considered efficient